Patterns of planktonic foraminiferal extinctions and eclipses during Oceanic Anoxic Event 2 at Eastbourne (SE England) and other mid-low latitude locations - Francesca Falzoni; Maria Rose Petrizzo (Cretaceous Research, 2020)
The latest Cenomanian Oceanic Anoxic Event (OAE) 2 represents one of the most extreme perturbations of the global carbon cycle. Planktonic foraminiferal events, variations in the taxonomic composition of assemblages (e.g., appearances, extinctions, temporary crisis of certain taxa) and their correlation with changes in the physico-chemical properties of surface waters are essential to reconstructing the consequences of OAE 2 on this group of calcareous microfossils. We present the results of a high-resolution biostratigraphic and taxonomic study of planktonic foraminifera performed at Eastbourne (SE England), representing the most expanded, complete and well-calibrated OAE 2 record in Europe. In this stratigraphic section, we identify a sequence of step-wise extinctions (i.e., Thalmanninella and Rotalipora species, and “Globigerinelloides” bentonensis) that are followed by an eclipse (temporary disappearance) of planispiral taxa and of hedbergellids with radially elongated chambers. These events are consistently found in approximately coeval stratigraphic intervals across low to mid-latitudes, suggesting that they were controlled by wide-scale environmental perturbations. Moreover, this study suggests that the extinction of rotaliporids might have been influenced by climate changes (i.e., warming for Thalmanninella and cooling during the Plenus Cold Event for Rotalipora) at the onset of OAE 2, whereas the eclipse of planispiral taxa and hedbergellids with radially elongated chambers during the second half of OAE 2 was likely related to enhanced productivity and mixing of surface waters potentially associated to warming after the PCE for planispirals. Finally, we identify two short-range species (Muricohedbergella kyphoma and Praeglobotruncana plenusiensis n. sp.) that co-occur with boreal macrofossils at Eastbourne and might represent the first evidence for a planktonic foraminiferal PCE fauna. The long ranging species Praeglobotrucana gungardensis n. sp. is described as new.